What determines demographic growth in green anacondas? Strong interactions among vertebrates in a neotropical ecosystem - Rivas, Jesús A.; Jaremko-Wright, Will (Frontiers in Ecology and Evolution, 2023)
Trophic cascades can produce important effects on a community where some species may have strong effects on other parts of the community up, down the food chain, or both..both. Top predators are often controlled from the bottom- up by the abundance of their prey base while prey animals are often controlled from the top- down. Studies of trophic interactions in the tropics suggest that the trophic chains are longer because of the high productivity; and because of the hight diversity there is abundant intra guild redundancy which results in weak interactions. We studied the effect of bottom -up forces affecting the population of green Anaconda (Eunectes murinus) in the Venezuelan llanos; looking at net primary productivity, precipitation, and the abundance of an important prey item, Capybara (Hydrochaeris hydrochaeris) abundance. Our data show a strong interaction of these variables on the percentage of Anacondas that reproduce in a given year (here forth breeding ratio). ;iIn particular Capybara abundance has a strong effect on anacondas breeding frequency. Capybara abundance itself is also under strong bottom -up influence determined by precipitation and Net Primary Productivity. These strong interactions are not what is expected from a tropical ecosystem. We also found an unexpected strong influence of precipitation and primary productivity on Anaconda demography breeding ratio not related to the abundance of Capybara, likely affecting abundance of other prey or affecting non-trophic variables. This later evidence supports the notion that there is redundancy in tropical food chains and, strong as the effect of Capybara abundance might be, Anacondas do not entirely rely on them.